RGS2 is a feedback inhibitor of melatonin production in the pineal gland. Issue 9 (21st March 2013) - Matsuo, Masahiro; Coon, Steven L.; Klein, David C.
Abstract : The 24‐h rhythmic production of melatonin by the pineal gland is essential for coordinating circadian physiology. Melatonin production increases at night in response to the release of norepinephrine from sympathetic nerve processes which innervate the pineal gland. This signal is transduced through G‐protein‐coupled adrenergic receptors. Here, we found that the abundance of regulator of G‐protein signaling 2 (RGS2) increases at night, that expression is increased by norepinephrine and that this protein has a negative feedback effect on melatonin production. These data are consistent with the conclusion that RGS2 functions on a daily basis to negatively modulate melatonin production. Abstract : Rgs2 mRNA and protein increase at night in the pineal gland. A norepinephrine–cAMP mechanism controls Rgs2 mRNA and protein. RGS2 protein inhibits norepinephrine stimulation of melatonin production. RGS2 protein inhibits norepinephrine stimulation of Aanat expression. RGS2 is part of a negative feedback loop in the pineal gland.